Early Neonatal Outcome of Clinically Diagnosed Fetal Distress in Low Resource Areas (Medicine Today, 2021)
Introduction: Fetal distress is a high risk obstetric situation associated with increased perinatal morbidity and mortality. It is also a major contributor to operative interventions in the majority hospitals of developing countries. The objective of this study was to observe clinically diagnosed fetal distress and early neonatal outcome after delivery.Materials and Methods: This hospital based cross-sectional study was carried out in Department of Obstetrics and Gynecology at Bashundhara Addin Medical College Hospital, Keraniganj during the period of January to December 2019. 212 women in active phase of labor at term pregnancy who met the inclusion and exclusion criteria were enrolled. Fetal distress was diagnosed by abnormal FHR and /or presence of meconium in amniotic fluid after rupture of membrane. Neonatal outcome was assesss by 1st & 5th mins Apgar Scores after delivery, babies requiring immediate resuscitation and admission to neonatal care unit & recorded.Result: Among fetal distress 11.32% babies had Apgar score